2019
DOI: 10.1177/0091026018819025
|View full text |Cite
|
Sign up to set email alerts
|

Military Veterans in Federal Agencies: Organizational Inclusion, Human Resource Practices, and Trust in Leadership as Predictors of Organizational Commitment

Abstract: Military veterans comprise a significant demographic that is adding to the diversity of the U.S. federal workforce. Using data from the 2015 Federal Employee Viewpoint Survey, this study examined the relationship between organizational inclusion, human resource practices, trust in leadership, and organizational commitment among military veterans and nonveterans in federal agencies. Structural equation modeling showed the positive impact of organizational inclusion and human resource practices on organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…In the whole process organizational trust is the first outcome, influencing the employee commitment. This argument has been backed by several researchers revealing organizational trust to be the strong predictor of organizational commitment [28,[47][48][49].…”
Section: The Impact Of Csr On Aoc Mediated By Organizational Trustmentioning
confidence: 98%
“…In the whole process organizational trust is the first outcome, influencing the employee commitment. This argument has been backed by several researchers revealing organizational trust to be the strong predictor of organizational commitment [28,[47][48][49].…”
Section: The Impact Of Csr On Aoc Mediated By Organizational Trustmentioning
confidence: 98%
“…Our study confirms that applying development strategies for all employees implies better results in service performance. In fact, if an inclusion strategy is generated in talent management, the impact on employee commitment is clear [ 54 ]. Alternatively, it may be possible to establish an integrated model of inclusion and exclusion in public administration [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, TM in public sector organizations tends to embrace inclusion policies. Previous studies relate this inclusion to commitment in the organization [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that military service cultivates a strong propensity toward inherent trust in organizational leaders (Haynie, 2016). Employer actions supporting inclusion have the capacity to build on that trust, leading to increased employee engagement and organizational commitment (Downey et al, 2015; Liggans et al, 2019). Prior to ELMS, both employer and employee have established an implicit psychological contract regarding how each will behave if ELMS occurs.…”
Section: Literature Reviewmentioning
confidence: 99%